“La valoración del informe del equipo técnico y su incidencia en el establecimiento del régimen de tenencia, en los tramites de la Unidad Judicial de la Familia, Mujer, Niñez y adolescencia del cantón Riobamba, en el año 2015.” - Padilla Vilema, Sonia Pilar (2017)
Research has deepened tenure, which must be given in the case where the home is separated, because the father and mother no longer live in necessary it is determined what it will remain in the care of children, but it states the article cited that the custom of tenure does not imply the reduction of rights arising from parental authority. It should be understood that possession is a legal concept of juvenile law, aimed at preserving the integrity of minor children when breaking home occurs, providing daily care to that of the parents to provide better conditions for this work without the rights and obligations of both parents are altered. This research will determine the effect produced by the report of the technical team of the court, against the establishment of tenure. However, you should puntualizase in advance that within the tenure, justice administrators tend to approve the agreement reached by the parents, which usually occurs in divorce, this on the basis of the standard. The technical report contains analysis that the administrator of justice can not argue, as they are conclusions based on special knowledge, the judge to be a lawyer does not have, is in such a situation that the judge should take these findings and issue its decision based on they. Concluding that the report of the technical team of the court raises the possibility of collecting exams in social and psychological consequently to prove the inconvenience that the child is under the possession of one parent, the report should recommend the change of regime tenure.